1964
DOI: 10.1172/jci104968
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Iron to Reticulocytes by Synthetic Chelating Agents*

Abstract: Iron, once absorbed from the gastrointestinal tract, is distributed throughout the body by the specific iron-binding protein (IBP, transferrin, siderophilin) (1). Iron binding by IBP is presumed to be of a chelate type in which the hexacoordination capacity of the ferric ion is satisfied by linkage with three phenolic oxygens, one carboxyl group, and a bicarbonate ion on the remaining coordination position (2-4). Since IBP has been shown to have a highly selective ability to deliver iron to the immature red ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1965
1965
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 14 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…We used this procedure to establish that about 93% of the -Felabeled iron nitrilotriacetate added to preincubated transferrin in dilute solution was actually bound. This is important because iron nitrilotriacetate, itself, is an efficient source of iron for hemoglobin synthesis bv reticulocytes (Princiotto et al, 1964;Morgan, 1971). The demonstration of iron binding in this type of experiment, and especially for in vivo experiments, seems mandatory.…”
Section: Resultsmentioning
confidence: 99%
“…We used this procedure to establish that about 93% of the -Felabeled iron nitrilotriacetate added to preincubated transferrin in dilute solution was actually bound. This is important because iron nitrilotriacetate, itself, is an efficient source of iron for hemoglobin synthesis bv reticulocytes (Princiotto et al, 1964;Morgan, 1971). The demonstration of iron binding in this type of experiment, and especially for in vivo experiments, seems mandatory.…”
Section: Resultsmentioning
confidence: 99%
“…In hemolytic anemia, for example, the biliary iron in humans increases Sfold (4). We have also shown that uptake of iron by the reticulocyte in an in vitro system can be sharply modified by the nature of the iron chelate (7). We have also shown that uptake of iron by the reticulocyte in an in vitro system can be sharply modified by the nature of the iron chelate (7).…”
mentioning
confidence: 69%
“…The significant structural features which brought about this result were the net neutral charge and lipid solubility of the iron chelates (7,16). Support for this view is provided by the fact that introduction of a charged anionic site into the parent molecular structure brings about a complete disappearance of the ability of the compounds to transport iron into the bile.…”
Section: Fig 7 Eddha Comdounds Structural Formulae Iron Binding Ocmentioning
confidence: 99%
“…Ferrioxamine and ferric N,.V' ethylenebis-( a imino-2 -hydroxy-5-chlorophenylacetate) (FeCI-EDDHA) are two iron chelates of differing molecular architecture whose iron binding strength exceeds that of iron transferrin (3,4 ) . The present study suggests that the molecular environment of the metal is a major determinant in its biological fate.…”
mentioning
confidence: 99%
“…Information about the composition of meconium in meconium ileus (MI) is accumulating (1)(2)(3)(4)). An early report ( 1) indicated that MI meconium contained similar water, 13 times more trichlmacetic acid (TCA)-insoluble nitrogen, and 4 times less carbohydlrate than is found in no& m m nium.…”
mentioning
confidence: 99%